USFDA-GUIDELINE BASED VALIDATION OF TESTING METHOD FOR RIFAMPICIN IN INDONESIAN SERUM SPECIMEN - Tri Joko Raharjo; Tri Wahyudi; Sismindari Sismindari (Indonesian Journal of Chemistry, 2010)
Regarding a new regulation from Indonesia FDA (Badan POM-RI), all new non patent drugs should show bioequivalence with the originator drug prior to registration. Bioequivalence testing (BE-testing) has to be performed to the people that represented of population to which the drug to be administrated. BE testing need a valid bio-analytical method for certain drug target and group of population. This research report specific validation of bio-analysis of Rifampicin in Indonesian serum specimen in order to be used for BE testing. The extraction was performed using acetonitrile while the chromatographic separation was accomplished on a RP 18 column (250 × 4.6 mm i.d., 5 µm), with a mobile phase composed of KH2PO4 10 mM-Acetonitrile (40:60, v/v) and UV detection was set at 333 nm. The method shown specificity compared to blank serum specimen with retention time of rifampicin at 2.1 min. Lower limit of quantification (LLOQ) was 0.06 µg/mL with dynamic range up to 20 µg/mL (R>0.990). Precision of the method was very good with coefficient of variance (CV) 0.58; 7.40 and 5.56% for concentration at 0.06, 5, 15 µg/mL, respectively. Accuracies of the method were 3.22; 1.94; 1.90% for concentration 0.06, 5 and 15 µg/mL respectively. The average recoveries were 97.82, 95.50 and 97.31% for concentration of rifampicin 1, 5 and 5 µg/mL, respectively. The method was also shown reliable result on stability test on freezing-thawing, short-term and long-term stability as well as post preparation stability. Validation result shown that the method was ready to be used for Rifampicin BE testing with Indonesian subject.